Microstructure and Optical Bandgap of Cobalt Selenide Nanofilms - Ghobadi, Nader; Hafezi, Fatemeh; Naderi, Sirvan; Amiri, Fatemeh; Luna, Carlos; Arman, Ali; Shakoury, Reza; Ţălu, Ştefan; Rezaee, Sahar; Habibi, Maryam; Mardani, Mohsen (Semiconductors (Woodbury, N.Y.), 2019)
The purpose of this research is to explore the properties of CoSe nanostructured thin films on glass substrates prepared by a chemical solution deposition method. Special attention is given to study the effects of precursor concentrations (Cobalt(II) acetate, Ammonia and Sodium Selenosulphite), fixing the Co:Se concentration ratio, on the grainy structure and optical properties of the resulting thin films. The structural, chemical composition and morphological characteristics were investigated by X-ray diffraction (XRD), energy dispersive X-ray microanalysis (EDX) and scanning electron microscopy (SEM), respectively. The optical properties were determined by UV–visible spectroscopy determining the optical band gap energy ( E g ). According to these results, the average particle diameter was decreased from 119 to 42 nm as the precursor salt concentration was decreased from 0.3 to 0.1 M, being the bigger nanoparticles more spherical. With the reduction of the particle size, a blue shift in the absorption peaks of the UV–visible spectra and an increment of their optical band gap energy (from 1.8 to 3.6 eV) occurred due to confinement effects.